Skin lymphoma the illustrated guide - Cerroni, Lorenzo (Wiley Blackwell, 2020)
"Many things have changed since 2014, when I completed the previous edition of this book. The World Health Organization (WHO) published in 2017 an update of the Classification of Tumours of Haematopoietic and Lymphoid Tissues, and in 2019 the European Organization for Research and Treatment of Cancer (EORTC), together with a WHO panel, published the first update since 2005 of the Classification of cutaneous lymphomas. In the new classifications all entities of cutaneous lymphomas have been updated, and some new ones were added. In this context, the book has been modified to reflect the new classification schemes. Molecular data are being increasingly used for diagnosis and classification of haematological malignancies, particularly for precise categorization of leukemias. On the other hand, access to state-of-the-art molecular techniques is still very limited: in fact, the vast majority of colleagues who report cases of cutaneous lymphoproliferative disorders make diagnoses based mostly on histopathological and phenotypical features combined with clinical aspects, thus the core of the book is still focused on a traditional clinicopathological approach to diagnosis. All relevant molecular data, of course, are discussed as well"--..
Includes bibliographical references and index